PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA KELAS IX SMP - Gutomo Wibi Ananggih; Ipung Yuwono; I Made Sulandra (Jurnal Kajian Pembelajaran Matematika, 2017)
Based on observations found that students can not explain the concept that already taught and also can not give examples of problems in everyday life related to the concept being taught. It shows that students do not have the ability to be an indicator of understanding. Based on interviews found that teachers often use the problem-based learning, but in the implementation tends to the teacher centered learning. To solve the that problems then held action classroom  research that used problem-based learning. With problem-based learning can enhance an understanding that shown by student have an ability to correspond with the seven indicators of understanding. Problem-based learning that has been able to increase the students' understanding of mathematics consists of five stages, namely: a) Reading problems. b) Defining the problem. c) Find the idea "Brainstroming". d) Solve the problem. e) Share learning result. Learning has developed seven indicators of mathematical understanding, namely: interpretation, exampling, classify, summarize, inferring, comparing, and explaining. Each indicator score, then score is accumulated into a final score. Resulting 83% of all students, ie 29 of 35 the number of classes students have had a score of more than or equal to 75. In fact, there are two students who received a score of 100.